Developing knowledge management strategies to create sustainable development at King Khalid University - Siralkhatim, Abeer Bakri; Ali, Rogia Tayb; Awad, Salwa Derar; Osman, Alwia Saeed (Journal of Economic, Administrative and Legal Sciences, 2021)
The research aimed at know the cognitive management strategies and its role in knowledge skills activation at Saudi’s universities to make sustainable development. and to identify applying cognitive management strategies realty as a contemporary management concept that affects the ability of institutions to achieve their goals. to provide some recommendations to specialists to enhance education strategies and policies in Saudi universities to afford society with skills that create sustainable development and work to improve society in a healthy and economic way. The importance of the research is in the higher education institutions are working on providing the comprehensive professional development requirement from the skilled humans elements to fit revolution’s age. and the knowledge management gains great importance, where it helps it to meet the challenges through develop its capacity on the searching, discovering, innovation, the challenges facing and creation of an enabling environment which motivates its knowledgeable employees to release their knowledge and to help the institution reach its goals. And relating the knowledges and experiences to what enabling the organization’s development and growth as one entity according to the modern- day requires. Main results: Knowledge management improves the process of strategic planning and decision- making, which helps create sustainable development. And Providing employees with the right ways to organize the knowledge available to them and make use of it to create sustainable development. and Knowledge management works to improve the level of efficiency and effectiveness of administrative services provided at the university and reduce their costs. Main recommendations: Adopting rational policies at King Khalid University that work to consolidate the values ​​and institutional frameworks that support the knowledge society. And Spreading the culture of education for all at all levels in a way that enables society, women and men alike, to participate actively and positively in creating sustainable development in various areas of life. And Keeping pace with the various developments in the fields of education and the transition to a knowledge society that requires quality education that takes into account the current data and the needs of society.